FAKTOR PENYEBAB RENDAHNYA KETERLIBATAN ANGGOTA PADA EKSTRAKURIKULER PALANG MERAH REMAJA (PMR) DI SMA N 13 PADANG - Friska; Sarbaitinil; Sri Rahmdani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low level of student participation in the Red CrossYouth (Palang Merah Remaja or PMR) extracurricular activity at SMA N 13 Padang.PMR serves as a forum for fostering social and humanitarian values amongstudents. However, data show that the number of PMR participants is relatively lowcompared to other extracurricular activities. The purpose of this study is to describeand understand the factors contributing to the low level of student participation inPMR. This research employed a qualitative approach with a descriptive type. Datawere collected through observation, in-depth interviews, and document analysis.The informants consisted of active and passive PMR members, students involvedin other extracurricular activities, the PMR advisor, and the vice principal for studentaffairs. The theoretical framework used was B.F. Skinner’s behaviorist theory. Thefindings indicate that the factors causing low student participation in PMR fall intotwo categories: internal and external. Internal factors include low personalmotivation, difficulty managing time, and feelings of being unappreciated. Externalfactors include the perception that PMR is an extracurricular activity for females, thesuboptimal involvement of the advisor, and inconsistent training schedules. Thesefactors collectively influence students’ decisions to be inactive or not to participatein PMR activities.